(untitled) (Journal of Economic Research & Business Administration, 2016)
Numerous crises which modern society faced, generate need of search of more perfect ways of development. The main components of a sustain able development are ecosystem approach to management of natural re sources, elimination of noneffective production, use of alternative energy sources today. The concept of «green» economy as one of the most impor tant instruments of achievement of a sustainable development gains the increasing popularity and is widely discussed at large international forums worldwide. Experience of world leaders in the field of «green» technolo gies and «green» body height, such as South Korea, Germany, Denmark, the USA, clearly demonstrates a positive contribution of model of «green» economy to a sustainable development.